Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 13 peer-reviewed papers on data, software, education, and a tribute to Ralph Peck. Topics include: the value of data; student learning enhancement; and observational methods for design. GSP 314 will be of interest to researchers and practitioners in all areas of geotechnical engineering.
Keywords: Peck, Ralph B. -- (Ralph Brazelton); Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Geotechnical engineering -- Data processing -- Congresses.; elektronické knihy; electronic books